Tube feet dynamics drive adaptation in sea star locomotion - Amandine Deridoux; Sina Heydari; Stanislav. N. Gorb; Eva Kanso; Patrick Flammang; Sylvain Gabriele (Proceedings of the National Academy of Sciences, 2026)
Sea stars use hundreds of tube feet on their oral surface to crawl, climb, and navigate complex environments, despite lacking a central brain. While tube foot morphology and function as muscular hydrostats are well described, the mechanisms that coordinate their collective dynamics remain poorly understood. To investigate these dynamics, we employed an optical imaging method based on frustrated total internal reflection (FTIR) to visualize and quantify tube foot adhesive contacts in real time in the species Asterias rubens across individuals spanning a wide size range. Our results reveal an inverse relationship between crawling speed and tube foot adhesion time, indicating that sea stars regulate locomotion by modulating contact duration in response to mechanical load. To test this, we conducted perturbation experiments using 3D-printed backpacks that increased body mass by 25 and 50%, along with biomechanical modeling of decentralized feedback control of the tube feet. The added load significantly increased adhesion time, supporting the role of a load-dependent mechanical adaptation. We further investigated inverted locomotion, both experimentally and through simulation, and found that tube feet adjust their contact behavior when the animal is oriented upside down relative to gravity. Together, these findings demonstrate that sea stars adapt their locomotion to changing mechanical demands by modulating tube foot–substrate interactions, revealing a robust decentralized control strategy in a brainless organism and highlighting general principles of distributed control in biology and soft robotics.